Linking Competency Based Leadership To Organizational Citizenship Behavior: Moderating Role Of Commitment In Nurses - Boni Lambang Pramana (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study is an explanatory quantitative study that aims to examine the causal relationship between competence, Organizational Citizenship Behavior, organizational commitment, and nurse performance in South Konawe Regency. Data was collected through a closed-ended questionnaire with a five-level Likert scale from strongly disagree to strongly agree. The instruments are compiled based on theories and findings of previous research, then evaluated through validity and reliability testing to ensure that each indicator is able to measure constructs accurately and consistently. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares because it is able to test the relationship between variables simultaneously, is more flexible to the characteristics of the data, and is suitable for research models with many indicators. Data processing is carried out using the latest version of SmartPLS with the evaluation stages of measurement models and structural models. The results of the analysis showed that organizational commitment did not have a significant direct effect on nurse performance. On the other hand, competence has been shown to have a positive and significant effect on performance, and has a very strong influence on Organizational Citizenship Behavior. Organizational Citizenship Behavior has also been shown to have a positive and significant effect on performance. In addition, organizational commitment plays a role as a moderator that strengthens the influence of Organizational Citizenship Behavior on performance, so that the impact of extra role behavior on performance becomes greater when nurse commitment is high. These findings confirm that improving nurse performance needs to be directed at strengthening competencies and forming Organizational Citizenship Behavior, and supported by organizational strategies that increase commitment so that results are more optimal.